Drone Equipment and Configuration for Detecting Theft in Telecommunication Infrastructure - Njoku, C. O.; Gambo, A. V.; Bello, Y. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2025)
Drone aircrafts, also known as an Unmanned Aerial Vehicle (UAV) or Unmanned Aircraft Systems (UAS) has gained more importance in environmental monitoring as well as in telecommunication infrastructure theft response around the world. The study aims at identifying the type of sensors that can be mounted on drones for effective telecommunication infrastructure theft detection and prevention. The various parts of drone and configuration were tested. Sensors capable of detecting telecommunication infrastructures in the visible, infra-red, near infra-red, laser fluoro-sensor were all evaluated. The ability of the UAV to continuously and successfully patrol along or beside telecommunication infrastructure reveals that it takes about 5 minutes for the UAV to complete a programmed 150m autonomous patrol. During power test, result showed that for every 150m programmed patrol, 15 minutes of solar charging is required to restore the battery back to its initial voltage. It was concluded that a drone can properly be used for telecommunication infrastructure theft response operations. Appropriate sensors mounted on the drone can detect telecommunication infrastructure theft and can also access locations which are not readily accessible and other aerial patrol platform. The limitation of drones is the payload capability and its inability to operate well in windy weather since data collection with drone are faster, cheaper and easier during telecommunication infrastructure theft response operations. It is highly recommended to mount the suitable sensor capable of detecting telecommunication theft and vandalization even during nighttime operations.